2017
DOI: 10.3847/1538-4357/aa607f
|View full text |Cite
|
Sign up to set email alerts
|

The Stochastic X-Ray Variability of the Accreting Millisecond Pulsar MAXI J0911–655

Abstract: In this work I report on the stochastic X-ray variability of the 340 Hz accreting millisecond pulsar MAXI J0911-655. Analyzing pointed observations of the XMM-Newton and NuSTAR observatories I find that the source shows broad band-limited stochastic variability in the 0.01 − 10 Hz range, with a total fractional variability of ∼ 24% rms in the 0.4 − 3 keV energy band, which increases to ∼ 40% rms in the 3 − 10 keV band. Additionally a pair of harmonically related quasi-periodic oscillations are discovered. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…XTE J1701-462; Bu et al 2015). The rms spectra of broad-band noise components of NS increase with energy in some cases (Bu et al 2015;Bult 2017, studying XTE J1701-462 and MAXI J0911-655, respectively), as MAXI J1727-203 did during most of the outburst. Unfortunately, neither of those works present the evolution of the rms spectra during a whole outburst, so at the moment we cannot compare the evolution of these sources and that of MAXI J1727-203.…”
Section: Nature Of the Compact Object In Maxi J1727-203mentioning
confidence: 93%
“…XTE J1701-462; Bu et al 2015). The rms spectra of broad-band noise components of NS increase with energy in some cases (Bu et al 2015;Bult 2017, studying XTE J1701-462 and MAXI J0911-655, respectively), as MAXI J1727-203 did during most of the outburst. Unfortunately, neither of those works present the evolution of the rms spectra during a whole outburst, so at the moment we cannot compare the evolution of these sources and that of MAXI J1727-203.…”
Section: Nature Of the Compact Object In Maxi J1727-203mentioning
confidence: 93%
“…In the current work we are only interested in the broad picture and to estimate the Poisson level, but we found no significant effect on the resulting PDS. we defer detailed analyses of our PDS to future work (but see already Ferrigno et al (2017) and Bult (2017) for such detailed studies for IGR J00291+5934 and Swift J0911.9-6452, respectively). To determine the strength of the noise components we observed in the PDS, we calculated the integrated noise strengths between 9.765625 × 10 −4 and 128 Hz (2 −10 -2 7 Hz).…”
Section: X-ray Timing Analysismentioning
confidence: 99%
“…Recently Bult (2017) suggested that the PDS obtained (using XMM-Newton data) during the 2016 outburst of another AMXP, Swift J0911.9-6452, resembled that of IGR J00291+5934. Therefore, we also included this source in our analysis and we confirm the noise properties reported for this source by Bult (2017).…”
Section: Igr J00291+5934 and Swift J09119-6452mentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recently the AMXP MAXI J0911-655 has been shown to exhibit a similar broad noise structure, but with LF QPOs that fall along the expected frequency relation (Bult 2017), casting doubt on this interpretation.…”
Section: The 20 Mhz Qpomentioning
confidence: 99%